Breast Cancer Early Detection Training Through Correct Sadari and Sadanis to Midwifes and Nurses - Bambang Arianto; Een Hendarsih; Pravica Juti Arumasari (Journal of Community Medicine and Public Health Research)
Breast cancer ranks first in terms of the number of cancers in Indonesia and is among the first contributors to cancer deaths. This is because 70% of the cases are detected at an advanced stage. After finding a lump in her breast, a patient does not necessarily see a doctor immediately. The cause of the problem is the lack of public knowledge about breast cancer. Therefore, prompt efforts are needed to solve this problem. Training for health workers, including midwives and nurses, in direct contact with the community regarding early detection and breast cancer therapy is essential. The hope is that midwives and nurses will become breast cancer health cadres through counseling, early detection, and treatment in the community. The results of this activity are increased knowledge among midwives and nurses about breast cancer, its early detection, and early treatment, which correlates with decreased delays in treatment